STUDI HISTOLOGI RUMEN, RETIKULUM DAN OMASUM SAPI SUMBA ONGOLE (Bos indicus) - Lucia D. Amleni; Filphin A. Amalo; Inggrid Trinidad Maha; Yulfia N. Selan (JURNAL KAJIAN VETERINER, 2019)
Sumba ongole cattle (Bos indicus) are one of the local cattle breed in Indonesia. Cattle have a forestomach which consists of rumen, reticulum and omasum. The functions of the forestomach are to digest food, ferment and absorb carbohydrates. This research aimed to determine the histological structure of rumen, reticulum and omasum sumba ongole cattle. Six samples of rumen, reticulum and omasum were collected from slaughter East Sumba. These samples were fixed in 10% formalin and then stain with HE. The histological results showed that the rumen, reticulum and omasum have four layers was the tunica mucosa, the submucosa, the muscularis and the serosa. The tunica mucosa rumen consists of lamina epithelia which composed of stratified squamous keratinized epithelium, lamina propria have connective tissue and blood vessels. The lamina muscularis mucosa composed of smooth muscle was absent in rumen mucosa, while tunica mucosa of reticulum and omasum have a lamina epithelia, lamina propria and lamina muscularis mucosa. The tunica submucosa rumen, reticulum and omasum have connective tissue, veins, arteries, capillaries and fibroblast nuclei. The tunica muscularis rumen, reticulum and omasum have inner circular and outer longitudinal muscular. The tunica serosa rumen, reticulum and omasum consist of blood vessels, loose connective tissue and adipose tissue.